2017
DOI: 10.1016/j.ygyno.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

A universal genetic testing initiative for patients with high-grade, non-mucinous epithelial ovarian cancer and the implications for cancer treatment

Abstract: Objective Genetic counseling (GC) and germline genetic testing (GT) for BRCA1 and BRCA2 are considered standard of care for patients with high-grade, non-mucinous epithelial ovarian, fallopian tube, and primary peritoneal cancers (HGOC). We describe a universal genetic testing initiative to increase the rates of recommendation and acceptance of GC and GT to greater than 80% for patients with HGOC at our institution. Methods Data from a consecutive cohort of patients seen in our gynecologic oncology clinics b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 19 publications
4
62
0
2
Order By: Relevance
“…In previous trials, strategies including EMR changes, workflow changes, care integration, and patient and provider education have resulted in a 40% to 352% increase in rates of genetics referral. 14,15,17,18 Another approach is BRCA1/2 testing of OVCA tumor tissue. 19 Pilot testing has found somatic GT to be feasible, effective, and acceptable to patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…In previous trials, strategies including EMR changes, workflow changes, care integration, and patient and provider education have resulted in a 40% to 352% increase in rates of genetics referral. 14,15,17,18 Another approach is BRCA1/2 testing of OVCA tumor tissue. 19 Pilot testing has found somatic GT to be feasible, effective, and acceptable to patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…Various medical centres have different levels of human and financial resources available to support the implementation and validation of new genetic testing and/or referral practices. An American study demonstrated that even a multipronged approach, which included embedding a genetic counsellor into oncology clinics, genetics review of medical records to identify eligible patients and oncologist-ordered genetic testing, did not result in 100% genetic testing rates for patients with ovarian cancer 50. A possible solution, as an adjunct or in replacement to the current models, is the implementation of reflexive tumour testing of all non-mucinous epithelial ovarian cancers as a strategy to eliminate potential physician, patient, geographic and system barriers 16 26 51.…”
Section: National Priorities To Improve Assessment and Testing For Almentioning
confidence: 99%
“…Additional roles may also include genetic risk assessment, the identification of appropriate genetic referral, referral triage, and clinician education. One Australian and three American studies were identified ( Table 4 ) [ 55 , 56 , 57 , 58 ]. All four studies reported improvements in GC referral rates for breast or ovarian cancer patients.…”
Section: Resultsmentioning
confidence: 99%